Anti-corrosion steel with grade of 8.8 or above, segment bolt and preparation method of segment bolt
By optimizing chemical composition and tempering heat treatment process, corrosion-resistant steel of 8.8 or above is used to solve the problem of rusting of pipe sheet bolts in the tunnel environment, significantly improving corrosion resistance and meeting the requirements of complex tunnel environments.
Patent Information
- Application Number
- CN202411854471.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
Existing pipe sheet bolts are prone to rust in complex tunnel environments, which affects structural safety and lacks clear corrosion resistance standards in China.
The corrosion-resistant steel is adopted at 8.8 or above, and the chemical composition (such as the content of elements such as Cu, Ni, Sn, B) and the tempering and heat treatment process are optimized to form a dense rust layer and corrosion-resistant layer to improve the corrosion resistance of the material.
The corrosion resistance of the tube sheet bolts is significantly improved, with an average annual corrosion rate of less than 0.28mm/a. No red rust appears in the neutral salt spray test and humidity and heat test, meeting the performance requirements of the complex environment of the tunnel.
Smart Images

Figure BDA0005191443970000071 
Figure BDA0005191443970000081 
Figure BDA0005191443970000082
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fastening connection, and specifically relates to a corrosion-resistant steel material of grade 8.8 or above, a segment bolt and a preparation method thereof. Background Art
[0002] With the vigorous development of China's transportation construction, the amount of cross-river tunnels, undersea tunnels and mountain tunnels has increased year by year. Concrete segments and steel segments are often connected by segment bolts. The amount of segment bolts is large and the corrosion resistance is required to be high. Existing segment bolts are usually made of low-alloy steel (such as 20Cr, 40Cr) combined with surface treatment. However, due to the complex service environment of traffic tunnels, when the surface coating of low-alloy steel peels off, the exposed part of the segment bolt is easily exposed to corrosive ions in the environment (such as Cl - 、SO4 2- ) or gas undergoes chemical or electrochemical reactions, causing bolt corrosion. The corrosion of segment bolts has many effects on the shield lining structure. It not only reduces the cross-sectional area of the bolts themselves, but also causes concrete to rust, expand, crack, and damage. In addition, it also causes the bonding performance between the bolts and concrete to decrease, seriously affecting the safety of the tunnel structure.
[0003] At present, there is no clear standard in China requiring the corrosion resistance of segment bolts, but anti-corrosion technology for large-size bolt materials or similar materials has emerged. However, its corrosion resistance is insufficient and cannot meet the segment connection requirements in complex tunnel structure environments. Summary of the invention
[0004] The purpose of the present invention is to provide a corrosion-resistant steel material with a grade of 8.8 or above, a segment bolt and a preparation method thereof. The corrosion-resistant steel material provided by the present invention has a grade of 8.8 or above and has excellent corrosion resistance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a corrosion-resistant steel material of grade 8.8 or above, comprising the following chemical components in percentage by mass: C 0.25-0.29%, Si 0.24-0.30%, Mn 0.72-1.10%, Ni 0.10-0.36%, Cu 0.22-0.38%, Al 0.018-0.030%, Ti 0.01-0.05%, B 0.0008-0.0040%, Sn 0.015-0.100% and Fe balance.
[0007] Preferably, the corrosion-resistant steel material of grade 8.8 or above further comprises a multi-element alloy co-penetration layer; the multi-element alloy co-penetration layer covers the surface of the corrosion-resistant steel material of grade 8.8 or above; the thickness of the multi-element alloy co-penetration layer is not less than 80 μm, and the mass is not less than 11.2 g / m 2The multi-element alloy co-diffusion layer includes the following chemical components in percentage by mass: 75-80wt% zinc, 13-18wt% aluminum and the remainder chromium.
[0008] The present invention also provides a method for preparing the 8.8 or higher grade corrosion-resistant steel material described in the above scheme, comprising the following steps:
[0009] The raw steel is subjected to a tempering heat treatment after hot upsetting, wherein the tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the 8.8 or above grade corrosion-resistant steel; the raw steel includes the following chemical components in percentage by mass: C 0.25-0.29%; Si 0.24-0.30%; Mn 0.72-1.10%; Ni 0.10-0.36%; Cu 0.22-0.38%; Al 0.018-0.030%; Ti 0.01-0.05%; B 0.0008-0.0040%; Sn 0.015-0.100% and Fe balance.
[0010] Preferably, the hot upsetting temperature is 950-1050° C., the pressure is 430-510 KN, and the hot upsetting time is 2-3 s.
[0011] Preferably, the quenching temperature is 850-900° C., and the holding time is 45-60 min.
[0012] Preferably, the tempering temperature is 450-550° C., and the holding time is 60-90 min.
[0013] Preferably, the tempering heat treatment also includes surface treatment of the obtained product; the surface treatment is powder multi-component alloy co-infiltration surface treatment; the infiltration temperature of the powder multi-component alloy co-infiltration surface treatment is 300-350°C, and the infiltration layer thickness is not less than 80μm; the infiltration layer elements of the powder multi-component alloy co-infiltration surface treatment include 75-80wt% zinc, 13-18wt% aluminum and a remainder of chromium.
[0014] The present invention also provides the use of the corrosion-resistant steel with a grade of 8.8 or above described in the above scheme or the corrosion-resistant steel with a grade of 8.8 or above obtained by the preparation method described in the above scheme in the field of fastening connection.
[0015] The present invention also provides a segment bolt, which is prepared using the corrosion-resistant steel of grade 8.8 or above described in the above scheme or the corrosion-resistant steel of grade 8.8 or above obtained by the preparation method described in the above scheme.
[0016] The present invention also provides a method for preparing the segment bolts described in the above scheme, comprising the following steps:
[0017] The raw steel is subjected to hot upsetting and then to hot thread rolling and quenching and tempering heat treatment in sequence, wherein the quenching and tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the segment bolts; the raw steel includes the following chemical components in mass percentage: C 0.25-0.29%; Si 0.24-0.30%; Mn 0.72-1.10%; Ni 0.10-0.36%; Cu 0.22-0.38%; Al 0.018-0.030%; Ti 0.01-0.05%; B 0.0008-0.0040%; Sn 0.015-0.100% and Fe remainder.
[0018] The present invention provides a corrosion-resistant steel material of grade 8.8 or above. The present invention promotes the formation of a dense and stable rust layer on the surface of the material through the composite of Cu and Ni, hinders further corrosion, and improves the corrosion resistance of the material; the present invention can form a composite of SnO2 and graphite on the surface of the material as an anti-corrosion layer through trace Sn, greatly enhancing the corrosion resistance of the material; the present invention improves the hardenability of steel by optimizing the C content and adding a trace amount of B to meet the performance requirements of large-size tunnel segment bolts. The corrosion-resistant steel material of grade 8.8 or above provided by the present invention adopts specific elements at specific contents to achieve excellent corrosion resistance, good mechanical properties, and excellent comprehensive performance. The results of the embodiment show that in a 72h accelerated corrosion test in a NaCl solution at a constant temperature of 30°C, a pH value of 0.85, and a concentration of 10wt%, the annual average corrosion rate (CR) is ≤0.28mm / a.
[0019] The present invention also provides a method for preparing the 8.8 or higher grade corrosion-resistant steel material described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, high feasibility and low cost.
[0020] The present invention also provides the application of the 8.8 or higher grade corrosion-resistant steel material described in the above scheme or the 8.8 or higher grade corrosion-resistant steel material obtained by the preparation method described in the above scheme in the field of fastening connection. The 8.8 or higher grade corrosion-resistant steel material provided by the present invention has excellent corrosion resistance and is suitable for fastening connection, such as preparing M30-M36 segment bolts, and can especially meet the performance requirements of complex environments such as mountainous areas, river crossings or submarine tunnels.
[0021] The present invention also provides a segment bolt. Compared with the prior art, the segment bolt provided by the present invention can significantly improve the corrosion resistance under the same bolt performance grade condition, the average annual corrosion rate in the accelerated corrosion test is lower than 0.28 mm / a, no red rust is found on the surface of the specimen after 1600 hours of neutral salt spray test, and no red rust is found on the surface of the specimen after 890 hours of wet heat test.
[0022] The present invention also provides a method for preparing the segment bolts of the above solution. The preparation method provided by the present invention has low labor cost, good safety, and is suitable for industrial-scale production. DETAILED DESCRIPTION
[0023] The invention provides a corrosion-resistant steel material of grade 8.8 or above, comprising the following chemical components in percentage by mass: C 0.25-0.29%, Si 0.24-0.30%, Mn 0.72-1.10%, Ni 0.10-0.36%, Cu 0.22-0.38%, Al 0.018-0.030%, Ti 0.01-0.05%, B 0.0008-0.0040%, Sn 0.015-0.100% and Fe balance.
[0024] The 8.8 or higher grade corrosion-resistant steel provided by the present invention includes 0.25-0.29% C, specifically 0.25%, 0.26%, 0.27%, 0.28% or 0.29%. The present invention improves the strength and hardness of the material by adding the above content of C as the main strengthening element in the material, while ensuring the toughness and plasticity of the material.
[0025] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises 0.24-0.30% Si, specifically 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29% or 0.30%. The present invention adds Si as a reducing agent and a deoxidizing agent, and Si can also play a role of solid solution strengthening.
[0026] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises 0.72-1.10% Mn, specifically 0.72%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1.00%, 1.05% or 1.10%. The present invention mainly uses Mn as a desulfurizing agent by adding Mn; the present invention controls the Mn content within the above range, and can also avoid the tendency of Mn segregation to the grain boundary during the tempering process.
[0027] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises Ni 0.10-0.36%, specifically 0.10%, 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, 0.26%, 0.28%, 0.30%, 0.32%, 0.34% or 0.36%. By adding Ni, the present invention significantly increases the compactness of the inner rust layer of the material, shifts the corrosion potential of the material positively, and improves the acid resistance, alkali resistance and atmospheric corrosion resistance of the material; in addition, Ni can improve the toughness of the material, especially the low-temperature toughness.
[0028] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises 0.22-0.38% Cu, specifically 0.22%, 0.24%, 0.26%, 0.28%, 0.30%, 0.32%, 0.34%, 0.36% or 0.38%. The present invention adds Cu, which plays the role of activating the cathode in the corrosion process, prompting the material anode to be passivated, thereby slowing down the corrosion; at the same time, the inner rust layer is promoted to be dense and stable, and the corrosion is prevented from further occurring.
[0029] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises 0.018% to 0.030% Al, specifically 0.018%, 0.020%, 0.022%, 0.024%, 0.026%, 0.028% or 0.030%. The present invention refines the grains, improves the anti-oxidation performance of the material, and reduces the brittle transition temperature of the material by adding Al as a deoxidizing and nitrogen fixing agent.
[0030] The 8.8 or higher grade corrosion-resistant steel provided by the present invention comprises 0.01-0.05% Ti, specifically 0.01%, 0.02%, 0.03%, 0.04% or 0.05%. The present invention adds Ti as a carbide-forming element, which has a very strong solid solution strengthening effect and can significantly refine the grains.
[0031] The corrosion-resistant steel material with a grade of 8.8 or above provided by the present invention comprises 0.0008% to 0.0040% B, specifically 0.0008%, 0.0010%, 0.0015%, 0.0020%, 0.0025%, 0.0030%, 0.0035% or 0.0040%. By adding a trace amount of B, the hardenability of the material can be significantly improved.
[0032] The corrosion-resistant steel material of grade 8.8 or above provided by the present invention comprises 0.015-0.100% Sn, specifically 0.015%, 0.020%, 0.030%, 0.040%, 0.050%, 0.070%, 0.090% or 0.100%. Sn has always been considered as a harmful impurity element in steel materials, which affects the quality of steel materials, especially the quality of continuous casting billets, causes hot brittleness and temper brittleness of steel, produces cracks and fractures, and affects the welding performance of steel. However, the present invention has found that by adding a trace amount of Sn, a dense SnO2 and graphite protective layer can be formed on the surface of the material, which hinders the further occurrence of corrosion reaction and significantly improves the corrosion resistance of the material.
[0033] The corrosion-resistant steel material with a grade of 8.8 or above provided by the present invention includes a Fe surplus. Corrosion-resistant steel material inevitably contains impurities, and the present invention reduces the content of impurity elements P and S as much as possible, reduces their segregation on the grain boundary, and improves the grain boundary strength.
[0034] The 8.8 or higher grade corrosion-resistant steel provided by the present invention preferably further comprises a multi-element alloy co-infiltration layer; the multi-element alloy co-infiltration layer is covered on the surface of the 8.8 or higher grade corrosion-resistant steel; the thickness of the multi-element alloy co-infiltration layer is preferably not less than 80 μm, and the mass is preferably not less than 11.2 g / m 2 The multi-element alloy co-diffusion layer preferably comprises the following chemical components in percentage by mass: 75-80wt% zinc, 13-18wt% aluminum and the remainder chromium.
[0035] In the present invention, the content of zinc is preferably 75-80wt%, specifically 75wt%, 76wt%, 77wt%, 78wt%, 79wt% or 80wt%.
[0036] In the present invention, the aluminum content is preferably 13-18wt%, specifically 13wt%, 14wt%, 15wt%, 16wt%, 17wt% or 18wt%.
[0037] The present invention also provides a method for preparing the 8.8 or higher grade corrosion-resistant steel material described in the above scheme, comprising the following steps:
[0038] The raw steel is subjected to a tempering heat treatment after hot upsetting, wherein the tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the 8.8 or above grade corrosion-resistant steel; the raw steel includes the following chemical components in percentage by mass: C 0.25-0.29%; Si 0.24-0.30%; Mn 0.72-1.10%; Ni 0.10-0.36%; Cu 0.22-0.38%; Al 0.018-0.030%; Ti 0.01-0.05%; B 0.0008-0.0040%; Sn 0.015-0.100% and Fe balance.
[0039] The present invention performs hot upsetting on the raw steel. In the present invention, the raw steel is preferably round steel; the round steel is preferably prepared by hot rolling of steel ingots; the starting rolling temperature of the hot rolling is preferably 1150-1250°C, specifically 1200°C, and the final rolling temperature is preferably not less than 1050°C, specifically 1050°C, 1150°C, 1250°C or 1350°C.
[0040] In the present invention, the temperature of the hot upsetting is preferably 950-1050°C, specifically 950°C, 980°C, 1000°C, 1025°C or 1050°C; the pressure is preferably 430-510KN, specifically 430KN, 450KN, 477KN, 491KN or 510KN; the hot upsetting time is preferably 2-3s, specifically 2.5s.
[0041] After hot upsetting, the present invention performs a tempering heat treatment on the obtained hot upsetting piece, and the tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the 8.8 or above grade corrosion-resistant steel. In the present invention, the quenching temperature is preferably 850-900°C, specifically 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, and the holding time is preferably 45-60min, specifically 45min, 50min, 55min or 60min.
[0042] In the present invention, the cooling rate of the water cooling is preferably 200-240°C / s, specifically 200°C / s, 210°C / s, 220°C / s, 230°C / s or 240°C / s, and the final temperature is preferably 40-55°C, specifically 45°C or 50°C.
[0043] In the present invention, the tempering temperature is preferably 450-550°C, specifically 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 530°C or 550°C, and the holding time is preferably 60-90min, specifically 60min, 70min, 80min or 90min.
[0044] In the present invention, the cooling is preferably air cooling; the cooling rate is preferably 250-320°C / min, specifically 250°C / min, 270°C / min, 280°C / min, 300°C / min or 320°C / min, and the final temperature is preferably room temperature, specifically 25°C.
[0045] In the present invention, the tempering heat treatment preferably also includes surface treatment of the obtained product; the surface treatment is preferably powder multi-component alloy co-diffusion surface treatment; the infiltration temperature of the powder multi-component alloy co-diffusion surface treatment is preferably 300-350°C, specifically 300°C, 310°C, 330°C or 350°C, and the infiltration layer thickness is preferably not less than 80μm, specifically 80μm, 90μm, 100μm, 120μm, 150μm, 180μm or 200μm.
[0046] In the present invention, the diffusion layer elements of the powder multi-element alloy co-diffusion surface treatment preferably include 75-80wt% zinc, 13-18wt% aluminum and a remainder of chromium; the zinc content is preferably 75-80wt%, specifically 75wt%, 76wt%, 77wt%, 78wt%, 79wt% or 80wt%.
[0047] In the present invention, the aluminum content is preferably 13-18wt%, specifically 13wt%, 14wt%, 15wt%, 16wt%, 17wt% or 18wt%.
[0048] The present invention also provides the use of the corrosion-resistant steel with a grade of 8.8 or above described in the above scheme or the corrosion-resistant steel with a grade of 8.8 or above obtained by the preparation method described in the above scheme in the field of fastening connection.
[0049] The 8.8 or higher grade corrosion-resistant steel provided by the present invention has excellent corrosion resistance and is suitable for fastening connections, such as preparing M30-M36 segment bolts, and can especially meet the performance requirements of complex tunnel environments such as mountains, rivers or seabeds.
[0050] The present invention also provides a segment bolt, which is prepared using the corrosion-resistant steel of grade 8.8 or above described in the above scheme or the corrosion-resistant steel of grade 8.8 or above obtained by the preparation method described in the above scheme.
[0051] In the present invention, the length of the segment bolts is preferably 200-720 mm, and specifically can be 200 mm, 400 mm, 600 mm or 720 mm.
[0052] The segment bolts provided by the present invention can significantly improve the corrosion resistance under the condition of the same bolt performance grade. The average annual corrosion rate in the accelerated corrosion test is lower than 0.28 mm / a. No red rust is observed on the surface of the specimen after 1600 h of the neutral salt spray test and 890 h of the wet heat test.
[0053] The present invention also provides a method for preparing the segment bolts described in the above scheme, comprising the following steps:
[0054] The raw steel is subjected to hot upsetting and then to hot thread rolling and quenching and tempering heat treatment in sequence, wherein the quenching and tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the segment bolts; the raw steel includes the following chemical components in mass percentage: C 0.25-0.29%; Si 0.24-0.30%; Mn 0.72-1.10%; Ni 0.10-0.36%; Cu 0.22-0.38%; Al 0.018-0.030%; Ti 0.01-0.05%; B 0.0008-0.0040%; Sn 0.015-0.100% and Fe remainder.
[0055] In the present invention, the preparation parameters of the segment bolts are the same as the preparation parameters of the 8.8 or above corrosion-resistant steel described in the above scheme, the difference is that the temperature of the hot rolling is preferably 800-1050°C, specifically 800°C, 850°C, 900°C, 950°C, 1000°C or 1050°C.
[0056] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0057] Example
[0058] A 100kg vacuum induction furnace was used to smelt 3 furnaces of 8.8 or higher corrosion-resistant steel materials of the present invention (Examples 1 to 3) and 4 furnaces of comparative steel materials (Comparative Examples 1 to 4). At the same time, 3 furnaces of typical bolt steel 35VB, 40Cr and weathering bolt steel NHB8 were selected as comparative steel materials, and the specific components were shown in Table 1. The molten steel was cast into ingots and then rolled into Φ30 round steel. The round steel was hot-forged (temperature of 100°C, pressure of 480KN, and hot-forging time of 2.5s) for shaping, and then subjected to quenching and tempering heat treatment (wherein the cooling rate of water cooling was 236°C / s, the final temperature was 45°C, and the cooling rate of air cooling was 280°C / min, and the final temperature was room temperature). Surface treatment (the penetration temperatures of multi-component alloy co-penetration in Examples 1 to 3 and Comparative Examples 1 to 2 are 300°C, 310°C, 320°C, 340°C and 350°C, respectively, and the alloy components are 80wt%, zinc 15wt% aluminum and the balance chromium), processed into standard room temperature tensile specimens, standard V-neck Charpy impact specimens and hanging specimens (60mm×25mm×5mm), the specimens were subjected to tensile tests at room temperature, impact performance tests were performed at -20°C, and accelerated corrosion tests were performed for 72 hours. The conditions of the accelerated corrosion tests are shown in Table 2. The corrosion weight loss and annual average corrosion rate of each specimen were evaluated. The specific preparation conditions and test results are shown in Table 3.
[0059] Segment bolts were prepared using the round steel of Examples 1 to 3 and Comparative Examples 1 to 4, and hot thread rolling was performed before surface treatment. Other conditions were the same as above. The existing surface treatment process was used as a comparison. After different surface treatments, neutral salt spray tests (refer to GB / T 10125 "Artificial atmosphere corrosion test salt spray test") and wet heat tests (60±2°C, 95±3%RH, refer to GB / T2423.3 "Environmental testing Part 2: Test method Test Cab: Constant wet heat test") were performed. The corrosion resistance of the segment bolts was determined by the time when red rust appeared. The test results are shown in Table 4.
[0060] Table 1 Composition (wt%) of Examples 1 to 3, Comparative Examples 1 to 4 and Comparative Steel Materials
[0061]
[0062]
[0063] Table 2 Accelerated corrosion test conditions
[0064] Test solution NaCl (10 wt%) and HCl mixed solution, pH = 0.85 Test temperature 30℃ constant temperature Test time 72h Remark Replace the solution every 24 hours to keep the pH value stable
[0065] Table 3 Test results of Examples 1 to 3, Comparative Examples 1 to 4 and comparative steel materials
[0066]
[0067] It can be seen from Table 3 that the corrosion-resistant steel of grade 8.8 or above provided by the present invention has better strength and toughness as a whole, a tensile strength of more than 920 MPa, a yield strength ratio of more than 0.85, a low-temperature impact energy of -20°C KV2 not less than 130 J, better corrosion resistance, and a comprehensive performance significantly better than the comparative example.
[0068] Table 4 Segment bolt test results of Examples 1 to 3 and Comparative Examples 1 to 4
[0069]
[0070]
[0071] It can be seen from Table 4 that the segment bolts made of corrosion-resistant steel of grade 8.8 or above of the present invention have excellent corrosion resistance, and no red rust is observed on the surface of the specimen after 1600h of the neutral salt spray test, and no red rust is observed on the surface of the specimen after 890h of the wet heat test.
[0072] It can be seen from the above embodiments that the corrosion-resistant steel of grade 8.8 or above provided by the present invention has excellent corrosion resistance, good mechanical properties and excellent comprehensive performance.
[0073] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A corrosion-resistant steel material with a grade of 8.8 or above, characterized in that: The invention comprises the following chemical components in percentage by mass: C 0.25-0.29%, Si 0.24-0.30%, Mn 0.72-1.10%, Ni 0.10-0.36%, Cu 0.22-0.38%, Al 0.018-0.030%, Ti 0.01-0.05%, B 0.0008-0.0040%, Sn 0.015-0.100% and Fe balance.
2. The corrosion-resistant steel material of grade 8.8 or above according to claim 1, characterized in that: The corrosion-resistant steel material of grade 8.8 or above further comprises a multi-element alloy co-penetration layer; the multi-element alloy co-penetration layer covers the surface of the corrosion-resistant steel material of grade 8.8 or above; the thickness of the multi-element alloy co-penetration layer is not less than 80 μm, and the mass is not less than 11.2 g / m 2 The multi-element alloy co-diffusion layer includes the following chemical components in percentage by mass: 75-80wt% zinc, 13-18wt% aluminum and the remainder chromium.
3. The method for preparing the 8.8 or higher grade corrosion-resistant steel according to any one of claims 1 to 2, characterized in that: The following steps are involved: The raw steel is subjected to a tempering heat treatment after hot upsetting, wherein the tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the corrosion-resistant steel material of grade 8.8 or above; The raw steel comprises the following chemical components in percentage by mass: C 0.25-0.29%, Si 0.24-0.30%, Mn 0.72-1.10%, Ni 0.10-0.36%, Cu 0.22-0.38%, Al 0.018-0.030%, Ti 0.01-0.05%, B 0.0008-0.0040%, Sn 0.015-0.100% and Fe balance.
4. The preparation method according to claim 3, characterized in that: The temperature of the hot upsetting is 950-1050° C., the pressure is 430-510 KN, and the hot upsetting time is 2-3 seconds.
5. The preparation method according to claim 3 or 4, characterized in that: The quenching temperature is 850-900° C., and the holding time is 45-60 minutes.
6. The preparation method according to claim 3 or 4, characterized in that: The tempering temperature is 450-550° C., and the holding time is 60-90 minutes.
7. The preparation method according to claim 3, characterized in that: The tempering heat treatment also includes surface treatment of the obtained product; The surface treatment is powder multi-element alloy co-penetration surface treatment; The infiltration temperature of the powder multi-element alloy co-infiltration surface treatment is 300-350°C, and the thickness of the infiltration layer is not less than 80 μm; The elements of the infiltration layer of the powder multi-element alloy co-infiltration surface treatment include 75-80wt% zinc, 13-18wt% aluminum and the balance of chromium.
8. Use of the corrosion-resistant steel material with a grade of 8.8 or above as described in any one of claims 1 to 2 or the corrosion-resistant steel material with a grade of 8.8 or above obtained by the preparation method described in any one of claims 3 to 7 in the field of fastening connections.
9. A segment bolt, prepared by using the corrosion-resistant steel with a grade of 8.8 or above as described in any one of claims 1 to 2 or the corrosion-resistant steel with a grade of 8.8 or above obtained by the preparation method described in any one of claims 3 to 7.
10. The method for preparing the segment bolts according to claim 9, characterized in that: The following steps are involved: The raw steel is subjected to hot upsetting and then hot thread rolling and quenching and tempering heat treatment in sequence, wherein the quenching and tempering heat treatment includes quenching, water cooling, tempering and cooling in sequence to obtain the segment bolts; The raw steel comprises the following chemical components in percentage by mass: C 0.25-0.29%, Si 0.24-0.30%, Mn 0.72-1.10%, Ni 0.10-0.36%, Cu 0.22-0.38%, Al 0.018-0.030%, Ti 0.01-0.05%, B 0.0008-0.0040%, Sn 0.015-0.100% and Fe balance.